von Willebrand Factor and Aging - Konkle, Barbara A. (Seminars in Thrombosis and Hemostasis, 2014)
von Willebrand factor (VWF) plays critical roles in initiating primary hemostasis and extending the half-life of coagulation factor VIII in circulation. VWF levels increase with age and elevated levels are associated with an increased risk of venous thromboembolism and cardiovascular disease (CVD). Patients with von Willebrand disease (VWD) due to a deficiency or dysfunction of VWF may have symptoms that ameliorate with aging or may have exacerbation of their disease. Bleeding sites of particular challenge in the aging patient include gastrointestinal bleeding and hematuria. Some medications used to treat VWD should be used with special precaution in older patients, including desmopressin and VWF-containing factor concentrates. Patients with VWD may have some protection from CVD, but in those patients who develop CVD, management is very challenging, given the role of antiplatelet therapy as the mainstay of treatment.
Keywords: von Willebrand factor; von Willebrand disease; factor VIII; hemorrhage; thrombosis; aging